Letter and Poem from Carl D. Duncan to Patricia Whiting, October 27, 1964 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Dr. Carl D. Duncan presents an untitled poem and sends birhtday greetings to Patricia Whiting.